Pengembangan bahan ajar bahasa inggris e-book berbentuk flipbook bagi mahasiswa tadris IPA - Aria Indah Susanti; Wahab Syakhirul Alim; Riski Kurniawan; Dzurrotun Nashihah (Universitas Indraprasta PGRI, 2025)
One of the positive impacts of technology in the field of education is the availability of teaching materials in electronic form. In addition to electronic form, electronic teaching materials can also be displayed attractively such as Flipbooks. Flipbook are digital books with a book-like appearance that can contain text, videos, images, or animations. The purpose of this study is to develop e-Book English teaching materials in the form of Flipbooks for Science Education Students. The approach to this research is quantitative with the type of research Research and Development or commonly called development research. The development model adopted is the 4D model but the research was carried out in only three stages, namely definition (Define), design (Design), and Development (Develop). The results of the study showed that the results of expert validation stated that the development of e-book English teaching materials in the form of flipbooks was declared valid in 4 assessment aspects and very valid in 15 other assessment aspects. The results of small group trials on science education students stated that 5 assessment aspects were very appropriate/very appropriate and 5 other aspects were appropriate